Handover Analysis Of Data Services In Wireless Distribution System (Wds) Using IEEE 802.11ac Standards In Telecommunication Laboratory Polines - Arya Pitaka (JAICT, 2017)
Problems with limited WLAN coverage areas often become a constraint when users access the Internet by migrating. This final project contains an analysis of the effect of handover on the quality of data service with Quality of Service (QoS) parameter that is throughput, delay, jitter and packet loss. The Wireless Local Area Network (WLAN) 802.11ac networking system in the Telecommunication Laboratory of Semarang State Polytechnic area that supports the handover feature is built with the Wireless Distribution System (WDS) technique that is configured with Service Set Identifier (SSID), the same password and channel and the placement of Access Point (AP) with overlapping coverage areas in one roaming domain. The tool used is Wireshark obtained the results of the test that is the average throughput value on the download service of 12,94 Mbps, the upload service of 11,22 Mbps and video streaming service of 3,66 Mbps. The average value of delay in the download service is 0,99 ms, the upload service is 1,19 ms and the video streaming service is 3,07 ms. The average value of jitter on the download service is 0,36 ms, on the upload service of 0,35 ms and the video streaming service is 3,66 ms. The average value of packet loss on the download service is 2,57 %, the upload service is 5,08 % and the video streaming service is 7,03%